If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + -3) = 2(7x + -5) Reorder the terms: -4(-3 + 2x) = 2(7x + -5) (-3 * -4 + 2x * -4) = 2(7x + -5) (12 + -8x) = 2(7x + -5) Reorder the terms: 12 + -8x = 2(-5 + 7x) 12 + -8x = (-5 * 2 + 7x * 2) 12 + -8x = (-10 + 14x) Solving 12 + -8x = -10 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 12 + -8x + -14x = -10 + 14x + -14x Combine like terms: -8x + -14x = -22x 12 + -22x = -10 + 14x + -14x Combine like terms: 14x + -14x = 0 12 + -22x = -10 + 0 12 + -22x = -10 Add '-12' to each side of the equation. 12 + -12 + -22x = -10 + -12 Combine like terms: 12 + -12 = 0 0 + -22x = -10 + -12 -22x = -10 + -12 Combine like terms: -10 + -12 = -22 -22x = -22 Divide each side by '-22'. x = 1 Simplifying x = 1
| x^3(9)=81 | | 8-2x=3x+43 | | 6x-32=0 | | 7x+9=-79 | | br-1+6r=11 | | 5(k+3)=2(k+7)-5 | | 2-3a+7=8a+3-a | | 16x(2x-9)=4(8x+8) | | 4x+6=74 | | 16y=180 | | 2m+7=2m-9 | | 6x+58=0 | | 2(x-3)=-24 | | 3(y-2)=y+8 | | 10x-3=6x+39 | | a=-5n+2n | | 2x+1=53 | | 5x+64=180 | | 7(11x-8)=77x-10 | | 13.0x-180forx=50 | | 8g+6=9g-10 | | x+77+x+62+45=180 | | 2(3x-7)=(5x-6) | | 9(x+5)=108 | | (2x+43)=(2x-3) | | X+-16=9 | | 13x-1=8x+39 | | n^2=-n | | 3*2-5+4*3-8+5*2= | | x-4+1=-3-x | | 3+3u=18 | | 250+150x=300y |